System identification of a solar maximum power point tracking system for dual axis / Thomas Davion, Noorazlina Mohamid Salih and Mohd Shahrizan Mohd Said - Davion, Thomas; Mohamid Salih, Noorazlina; Mohd Said, Mohd Shahrizan (2019)
The project is on Maximum efficiency of a solar panel. As the sun is not constant at one place and by fixing the solar array at a place, maximum power generation is not possible. This project develops a solar power generation system using maximum power point tracking system to gain more direct sun light on Photovoltaic (PV) modules leads to enhanced energy yield. Therefore, tracking systems are implemented to improve the performance of PV system by tracking sun trajectory. The current design of Maximum Power Point Tracking (MPPT) trackers are more efficient than conventional single state solar power generation. Then by comparing two designs initially produced, Maximum Power Point Tracking (MPPT) tracking devices are found to be at better efficiency than static models. The system locates maximum- power generating point using an MPPT controller. The base line results of this study were obtained via physical implementation of simulated system to analyze the various parameters. The system then uses a quadratic-equation based algorithm that calculates the quadratic function corresponding to the maximum power generation point. With the advent of different applications of PV solar power, system planners have been implementing different strategies and techniques to maximize the output of solar system with commonly available technology in market. Additionally, various mathematical techniques were utilized to analyze the results gathered from the physical implementation. The results of this study are based on two types of analysis. The comparison of static Photovoltaic output graphs with real time measured values for the systems and a Dynamic Photovoltaic Maximum power point Solar Tracker (MPPT) system. Both PV systems were implemented practically to get appropriate results and mainly all the equipment and services utilized in installation are widely available in local market.